2018
DOI: 10.1111/1365-2664.13263
|View full text |Cite
|
Sign up to set email alerts
|

A landscape approach for cost‐effective large‐scale forest restoration

Abstract: Achieving global targets for forest restoration will require cost‐effective strategies to return agricultural land to forest, while minimizing implementation costs and negative outcomes for agricultural production. We present a landscape approach for optimizing the cost‐effectiveness of large‐scale forest restoration. Across three different landscapes within Brazil's Atlantic Forest biodiversity hotspot, we modelled landscape scenarios based on spatially explicit data on the probability of natural regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
9

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 46 publications
2
77
1
9
Order By: Relevance
“…By contrast, the absence of a relationship between the effects of active restoration on carbon storage and isolation suggests that active restoration could provide benefits for climate change mitigation in isolated and in well-connected fragments, at least over the relatively short timeframes (e.g., 10-15 yr) targeted by major climate change policies (United Nations 2015). Collectively, these findings underscore the importance of considering multiple components of recovery (Gatica-Saavedra et al 2017), and accounting for spatial heterogeneity in natural regeneration (Molin et al 2018), in prioritizing active and passive interventions within restoration strategies for degraded forests.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…By contrast, the absence of a relationship between the effects of active restoration on carbon storage and isolation suggests that active restoration could provide benefits for climate change mitigation in isolated and in well-connected fragments, at least over the relatively short timeframes (e.g., 10-15 yr) targeted by major climate change policies (United Nations 2015). Collectively, these findings underscore the importance of considering multiple components of recovery (Gatica-Saavedra et al 2017), and accounting for spatial heterogeneity in natural regeneration (Molin et al 2018), in prioritizing active and passive interventions within restoration strategies for degraded forests.…”
Section: Discussionmentioning
confidence: 84%
“…), and accounting for spatial heterogeneity in natural regeneration (Molin et al. ), in prioritizing active and passive interventions within restoration strategies for degraded forests.…”
Section: Discussionmentioning
confidence: 99%
“…A major advantage of natural regeneration as an ecological restoration approach is the substantially reduced implementation costs compared to tree planting , Cruz-Alonso et al 2019. In Atlantic Forest landscapes with relatively high forest cover, where natural regeneration is most likely, costs of site preparation and tree planting are reduced by 38% (Molin et al 2018). Because of these lower costs, considerably larger areas can be restored using assisted natural regeneration approaches compared to widespread tree planting (Chazdon and Guariguata 2016).…”
Section: Economic Benefits Of Naturally Regenerating Forestsmentioning
confidence: 99%
“…In agricultural landscapes, patches of forest regeneration are more likely to be found adjacent to existing old-growth forest remnants , and natural regeneration is more likely to occur and have better biodiversity outcomes in landscapes with more forest cover (Crouzeilles et al 2016(Crouzeilles et al , 2020. Deforested areas on steep slopes with less intensive prior land use and close to forest remnants are the most likely to regenerate spontaneously (Rezende et al 2015, Molin et al 2018). A systematic review of drivers of tropical forest cover expansion through natural regeneration found that proximity to forest remnants, steep slopes, high forest cover at the landscape scale and proximity to watercourses were the most important biophysical factors (Borda-Niño et al 2020).…”
Section: Natural Forest Regeneration In the Tropics And Subtropicsmentioning
confidence: 99%
“…Ecosystems heavily modified or displaced by agriculture may be at risk of ecological collapse due to the loss of biotic components or ecological functions (Keith et al 2013, Bland et al 2018. Ecological restoration of such ecosystems requires facilitation of natural regeneration processes, which is often augmented by large-scale, active revegetation programs (Vesk and MacNally 2006, Molin et al 2018, Rohr et al 2018. Ecological interventions are expensive and have high uncertainty, and conservation budgets are typically small (Curtis and Lockwood 2000, McLeod 2004, Cooke et al 2010, so an understanding of the processes underpinning success and failure is critical.…”
Section: Introductionmentioning
confidence: 99%